Mindfulness and Hasidic Modernism: Toward a Contemplative Ethnography - Seeman, Don (Religion and society, 2019)
Amid growing interest in mindfulness studies focusing on Buddhist and Buddhism-derived practices, this article argues for a comparative and ethnographic approach to analogous practices in different religious traditions and to their vernacular significance in the everyday lives of practitioners. The Jewish contemplative tradition identified with Chabad Hasidism is worth consideration in this context because of its long-standing indigenous tradition of contemplative practice, the recent adoption of mindfulness' practices or terminology by some Hasidim, and its many intersections with so-called Buddhist modernism. These intersections include the personal trajectories of individuals who have engaged in both Buddhist and Hasidism-derived mindfulness practices, the shared invocation and adaptation of contemporary psychology, and the promotion of secularized forms of contemplative practice. We argue that Hasidic modernism' is a better frame than neo-Hasidism' for comparative purposes, and that Hasidic modernism complicates the taxonomies of secularity in comparable but distinctive ways to those that arise in Buddhist-modernism contexts.